2010
DOI: 10.1007/s11661-010-0526-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermoelastic Martensitic Transformations Using a Phase-Field Model

Abstract: The mechanisms of face-centered cubic (fcc),face-centered tetragonal (fct) thermoelastic martensitic transformations (MTs) in Mn-rich Mn-Cu alloys were studied using a phase-field model. In this article, a phase-field model describing the martensitic transformation was developed with the capability of treating continuously varying temperatures under two boundary conditions. The analysis of various energies during the microstructural evolution reveals that the elastic strain energy is a resistant force in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For instance, within the Ginzburg-Landau theory [32], the primary order parameters may be used to describe either some components of the strain tensor or atomic shuffles. In the first approach, the free energy density is a polynomial in terms of strain components [33][34][35][36][37][38], while in the second approach, the free energy is a Landau polynomial in terms of atomic shuffles plus a linear or quadratic term which couples order parameters and the strain tensor [19,[39][40][41][42][43][44][45][46]. A third approach may be worth mentioning here, which uses the same order parameters as in the aforementioned second approach, but it couples the strain tensor components to the order parameter(s) through a 2-3-4 or higher-order polynomial [47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, within the Ginzburg-Landau theory [32], the primary order parameters may be used to describe either some components of the strain tensor or atomic shuffles. In the first approach, the free energy density is a polynomial in terms of strain components [33][34][35][36][37][38], while in the second approach, the free energy is a Landau polynomial in terms of atomic shuffles plus a linear or quadratic term which couples order parameters and the strain tensor [19,[39][40][41][42][43][44][45][46]. A third approach may be worth mentioning here, which uses the same order parameters as in the aforementioned second approach, but it couples the strain tensor components to the order parameter(s) through a 2-3-4 or higher-order polynomial [47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…(23). Additionally, they showed that conditions (24) and (26) for accuracy and stability will still hold true (condition (25) does not apply to the first-order problem because when the Y Y Y variables are dropped, the parameter β plays no role in the algorithm). The generalized-α algorithm permits optimal high-frequency dissipation by parameterizing α m and α f in terms of the spectral radius of the amplification matrix as ∆t → ∞, namely ̺ ∞ .…”
Section: Time Stepping Schemementioning
confidence: 99%
“…(23). Additionally, they showed that conditions (24) and (26) for accuracy and stability will still hold true (condition (25) does not apply to the first-order problem because when the Y Y Y variables are dropped, the parameter β plays no role in the algorithm).…”
Section: Time Stepping Schemementioning
confidence: 99%
See 1 more Smart Citation
“…However, the influence of different strain rates on microstructure and mechanical response of FePd samples on temperature-and stress-induced PTs was examined by using exclusively the isothermal model. Other 3D PF models have reported morphological evolution in spinodal decomposition [39], thermoelastic transformations [40] and decomposition of the supersaturated binary solid solution [41].…”
Section: Introductionmentioning
confidence: 99%